IMPLEMENTASI KEBIJAKAN KEBERADAAN PAMONG BELAJAR DAN PENILIK SUATU ANALISIS TERHADAP PERATURAN PERUNDANG-UNDANGAN - Sumanto, Sumanto (JIV-Jurnal Ilmiah Visi, 2010)
Policy for non formal education educators and personnel program (pamong belajar and penilik) covered on national education regulations. The objective of this policy analysis is to find out the substance and consistency of policy implementation for non formal education educators and personnel (pamong belajar and penilik). This study analyse the national, provincial and district government level policy on nonformal education educators and personnel on national level. This study concludes that the policy of nonformal education not comprehensif educators and personnel in national, provincial and district lever are not yet consistent.